1997
DOI: 10.1093/ajcn/66.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk viscosity on gastric emptying and lactose intolerance in lactose maldigesters

Abstract: The possibility of delaying gastric emptying and improving lactose digestion and tolerance by increasing milk viscosity was studied in 13 lactose maldigesters who ingested three test milks with different viscosities (range: 33-1892 mPa.s) in random order at intervals of 1 wk. Each test portion was 500 mL and provided approximately equal to 1900 kJ and 18 g lactose. The different viscosities were obtained by adding varying proportions of rice starch and maltodextrin to a basic milk formula. A combined [13C]glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
8
1
1
Order By: Relevance
“…The lengthening of the gastrointestinal transit time may be due to the more solid composition or viscosity of yoghurt. However, we failed to find any difference in gastric emptying of lactose tolerance between the milks of varying viscosity [93].…”
Section: Lactose Intolerancecontrasting
confidence: 73%
“…The lengthening of the gastrointestinal transit time may be due to the more solid composition or viscosity of yoghurt. However, we failed to find any difference in gastric emptying of lactose tolerance between the milks of varying viscosity [93].…”
Section: Lactose Intolerancecontrasting
confidence: 73%
“…High meal viscosity may delay gastric emptying and increase satiety (Marciani et al, 2000), but the extent of this effect is not clear (Vesa et al, 1997). Gastric emptying is delayed in cases of severe malnutrition and is associated with nausea, vomiting and gastric fullness (Franco, et al, 1985;Rigaud et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, controversy prevails with respect to whether gastric emptying is delayed in infants fed with thickened formula 4,15–18 . Fabiani et al .…”
mentioning
confidence: 99%
“…14 However, controversy prevails with respect to whether gastric emptying is delayed in infants fed with thickened formula. 4,[15][16][17][18] Fabiani et al reported that enrichment of infant formula with galactomannan did not change gastric emptying patterns in infants with uncomplicated GER. 17 Similarly, Vivatvakin and Buachum reported that thickening of formula with LBG did not change gastric emptying patterns.…”
mentioning
confidence: 99%